Problems of Conduct: An Introductory Survey of Ethics - Drake, Durant, 1878-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Problems of Conduct: An Introductory Survey of Ethics" by Durant Drake is a philosophical text written in the early 20th century. The work serves as an educational resource, designed for both college students and general readers interested in understanding ethics. Drake focuses on the evolution of morality, the psychological foundations of ethical obligations, and how moral principles guide individual and societal conduct. The opening of the book establishes a foundation for the exploration of ethics, framing moral philosophy as essential to understanding the differences between good and evil and guiding human actions. Drake emphasizes the importance of individual choice in moral decision-making, contrasting the instinctive behaviors found in primitive life with the conscious reflections prevalent in more developed civilizations. He outlines the necessity of studying ethics to navigate daily dilemmas effectively, develop personal ideals, and understand the underlying factors that drive moral behavior. Throughout the beginning, Drake sets the stage for deeper inquiries into the complex nature of morality, suggesting that an ethical framework is crucial for achieving a harmonious and meaningful life in society. (This is an automatically generated summary.)
The evolution of morality -- The origin of personal morality -- The origin of social morality -- Outward development: morals -- Inward development: conscience -- The individualizing of conscience -- Can we base morality upon conscience -- The theory of morality -- The basis of right and wrong -- The meaning of duty -- The judgment of character -- The solution of personal problems -- The solution of social problems -- Objections and misunderstandings -- Alternative theories -- The worth of morality -- Personal morality -- Health and efficiency -- The alcohol problem -- Chastity and marriage -- Fellowship, loyalty, and luxury -- Truthfulness and its problems -- Culture and art -- The mechanism of self-control -- The attainability of happiness -- Public morality -- Patriotism and world-peace -- Political purity and efficiency -- Social alleviation -- Industrial wrongs -- Industrial reconstruction -- Liberty and law -- Equality and privilege -- The future of the race.
Release date is 2004-05-01
Produced by Charles Aldarondo, Charles Franks and the Online Distributed Proofreading Team
Keywords: Ethics